Monitoring the effects of oxidative stress on the growth of Holstein bull calves using Diquat - Liu, Ting; Chen, Huan; Cairang, Dongzhu; Cheng, Shuru; Luo, Zhihao; Zhang, Ming; Casper, David P. (Frontiers in Veterinary Science, 2025)
BackgroundHolstein bull calves received a one-time intraperitoneal injection of Diquat to explore its effects on growth, body frame, blood oxidation indices, fecal scores, and pathogenic bacteria in weaned calves.MethodsA total of twelve 70-day-old Holstein bull calves with similar body weight (BW) and body condition were randomly assigned to one of four treatments. The treatments were as follows: Control: calves were injected with 0 mg/kg BW Diquat in 0.9% sterilized saline; treatments 6, 8, and 10 mg/kg BW Diquat, respectively. The experimental period lasted for 24 days. Measurements of BW, average daily gain (ADG), fecal scores, frame gains, fecal pathogen count, and blood samples for monitoring oxidative stress were collected on days 0, 6, 12, 18, and 24. Data were analyzed using a randomized complete block design, with days considered as a repeated measurement. In addition, exponential polynomial contrasts were used to assess the linear, quadratic, and cubic treatment responses.ResultsGrowth performance (BW) and ADG showed a cubic response (p < 0.02), initially decreasing and then increasing with higher Diquat dosages. Fecal scores and fecal ratios exhibited a quadratic response (p < 0.02), rising at a diminishing rate as Diquat injection dosages increased. Frame gains for body slope, body length, hip height, and abdominal girth displayed a linear decrease (p < 0.03) with increasing Diquat injection dosages. Serum aspartate aminotransferase, glutathione, total antioxidant capacity, catalase, malondialdehyde, cortisol, and noradrenaline concentrations revealed a linear increase (p < 0.01) in response to higher Diquat injection dosages, while alanine transaminase, superoxide dismutase, and glutathione peroxidase demonstrated a quadratic response (p < 0.02), increasing at a diminishing rate. Fecal Escherichia coli concentrations demonstrated a cubic response (p < 0.01), while Staphylococcus aureus and Salmonella-Shigella demonstrated linear increases (p < 0.01) with increasing Diquat dosages.ConclusionDiquat injection induced oxidative stress, leading to reduced growth performance, along with increased serum oxidative stress indices, fecal scores, and fecal pathogens, a response that may persist for up to 24 days. An optimal dosage of 8 mg/kg BW is proposed as a benchmark for elucidating oxidative stress to evaluate future technologies aimed at reducing, eliminating, or preventing oxidative stress.